2004
DOI: 10.1111/j.1945-5100.2004.tb01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Chicxulub central crater structure: Initial results from physical property measurements and combined velocity and gravity modeling

Abstract: Abstract-The Chicxulub crater in Mexico is a nearly pristine example of a large impact crater. Its slow burial has left the central impact basin intact, within which there is an apparently uneroded topographic peak ring. Its burial, however, means that we must rely on drill holes and geophysical data to interpret the crater form. Interpretations of crater structures using geophysical data are often guided by numerical modeling and observations at other large terrestrial craters. However, such endeavors are hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Craters on Earth often display internal ring-like structures, but complications and uncertainties due to target heterogeneity, erosion and sedimentation, make it difficult to distinguish peak rings that are genetically linked to their extraterrestrial counterparts (8)(9). Seismic reflection data across the ~200-km diameter Chicxulub multi-ring impact structure revealed it to be the only terrestrial crater with an unequivocal and intact peak ring, with the same morphological structure as peak-ring craters on Venus, Mercury, the Moon, and other rocky bodies (10)(11)(12)(13)(14).…”
Section: Continental Scientific Drilling Program (Icdp)mentioning
confidence: 99%
“…Craters on Earth often display internal ring-like structures, but complications and uncertainties due to target heterogeneity, erosion and sedimentation, make it difficult to distinguish peak rings that are genetically linked to their extraterrestrial counterparts (8)(9). Seismic reflection data across the ~200-km diameter Chicxulub multi-ring impact structure revealed it to be the only terrestrial crater with an unequivocal and intact peak ring, with the same morphological structure as peak-ring craters on Venus, Mercury, the Moon, and other rocky bodies (10)(11)(12)(13)(14).…”
Section: Continental Scientific Drilling Program (Icdp)mentioning
confidence: 99%
“…The data misfit is calculated using both the gravity and travel-time misfit, and there is an extra step to convert between slowness (1/velocity) and density. We have used a suite of measurements [Vermeesch and Morgan, 2004] on core from drill holes within the post-impact sedimentary rocks, Cretaceous target rocks and impact breccias, to determine a best-fit equation for the conversion: density (in kg m -3 ) = -3478 × slowness (in 10 3 s m -1 ) + 3326 [Vermeesch, 2006;Vermeesch et al, 2008]. We have used a relatively large uncertainty of 1 mgal for the gravity (~5 % of the total anomaly) as we do not wish to over-fit the gravity data,…”
Section: Combined Travel-time and Gravity Inversionmentioning
confidence: 99%
“…1) revealed strong changes in seismic velocity across the crater, with a low-velocity-zone (LVZ) beneath the peak ring and a high-velocity-zone (HVZ) close to the crater center [Morgan et al, 2000;Christeson et al, 2001;Vermeesch and Morgan, 2004]. Resolution testing suggested that the final velocity model was robust in areas of good ray coverage , and that the top of the HVZ had a concave upward shape along well-constrained profiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data on physical properties have been reported from analyses on samples from borehole cores (e.g., Sharpton et al, 1996;Urrutia-Fucugauchi et al, 1996;Vermeesch and Morgan, 2004;Mayr et al, 2008;Elbra and Pesonen, 2011). Data are however limited to the upper formations of the carbonate sequences and breccias, which have been sampled in the boreholes.…”
Section: Methodsmentioning
confidence: 99%